Analisis Kesalahan Berbahasa Pada Proposal Kegiatan Pemberdayaan Masyarakat Penderita Hipertensi - Aura Meriska; Rosenta L Situngkir; Felicia Joice Sitinjak; Mustika Wati Siregar (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze language errors in proposals for empowerment activities for people with hypertension. Qualitative methods are used in this research to explore and understand language errors that may be contained in the proposal. The data analyzed is a proposal for community empowerment activities for people with hypertension collected from various trusted sources. The analysis is carried out using a qualitative approach, where the researcher will in-depth identify, categorize and analyze language errors contained in the proposal. It is hoped that the results of this research will provide a better understanding of language errors that often occur in proposals for empowerment activities for people with hypertension, so that they can contribute to improving the quality of these proposals. Keywords: analyze, errors, language, proposals